Leaf protein analyses in order to utilise the leaf shoot of artichoke - Kaszás, László; Fári, Miklós; Hodossi, Sándor; Domokos-Szabolcsy, Éva (Acta Agraria Debreceniensis, 2016)
The constat growth of the Earth’s population brings with itself a higher demand for food and protein not only in human nutrition but also for the feeding of livestock. Currently, the feed industry is mainly built onseed-based protein, wherethebaseplant is soybean, which is large lycovered by imports in Hungary, similar toother European countries. However, the long-term economically sustainable lifestock breeding demandschanges which has also worked out strategies. An alternative protein sources could be green leafy plants. In current work the Jerusalem artichokes as an alternative source of protein was studied, compared to alfalfa as a valuable protein plant. Our results indicate that fiber fraction ofJerusalem artichoke shootswas 34 to 37% after pressing in the autumn period while alfalfa slightly lower values were obtained (30%). On the other hand extracted green leaf protein concentration was higher in alfalfa than in Jerusalem artichoke. Along with this higher protein content could be measured from the leaf protein concentration of alfalfa and almost each amino acids were more, as well comparing to Jerusalem artichoke. Overall, the alfalfa proved to be advantageous as expected both in leaf protein extraction efficiency, both regarding the content of the protein in the Jerusalem artichoke. However, considering aminoacid composition and green biomass production, Jerusalem artichokecould be a promisingplant species asplant protein sourceinthefuture.